Integration of Customary Legal Values in Modern Legal Counseling in Local Communities - Junaidi Lubis; Melky Suhery Simamora; Irna Herliza Rizki; Fahmi Ruziq (Outline Journal of Community Development, 2024)
This community service aims to integrate the values of customary law into modern legal outreach within local communities. The primary objective of this activity is to enhance the understanding of customary communities regarding national law and to demonstrate the relevance of customary law within the national legal framework. The legal outreach was conducted with an approach sensitive to local culture, involving customary leaders, legal counselors, and community members in interactive sessions. The results of this service show significant improvement in the community's understanding of national law and their rights within the context of both customary and modern law. Before the outreach, the community's understanding of national law was only 45%, but after the outreach, it increased to 85%. Similarly, understanding of customary law and women's rights showed a significant increase. This program also encouraged active community participation in legal processes, both in resolving customary land disputes and in utilizing national legal mechanisms. However, challenges remain, including ignorance of more complex legal procedures and the need for policies that better support the integration of customary law into the national legal system. Moving forward, further collaboration between customary communities, legal counselors, and the government is expected to strengthen the implementation of fair and inclusive law.